Influence of surface treatment on the shear strength of Ultra Translucent Multi Layered Zirconia Katana (Research, Society and Development, 2022)
The aim of this study is to assess how shear strength of Ultra Translucent Multi Layered Zirconia Katana (UTML) is affected by the conditioning with 10% hydrofluoric acid combined with the current surface treatment protocol: air, primer containing 10-MDP, and cement. Samples of UTML Zirconia Katana were machined to measure 5x5x10 units of measurement, attached, and divided into two groups. In the control group, samples were treated with 27 um aluminum oxide blasting at 4 bars, application of Zr primer containing 10-MDP and, finally, cement Panávia V5. In the experimental group, samples were also treated with 10% hydrofluoric acid following blasting and prior to the primer application. The test specimens were submitted to shear mechanical strength test on a universal testing machine EMIC DL2000 (EMIC, São Paulo, Brazil), surface analysis with Scanning Electron Microscope (SEM) (Sputter Coaster Emitech, K450) and surface roughness. Results showed that the bond strength of specimens conditioned with acid was 41% higher (p = 0.031). Student’s t test showed that the samples conditioned with acid were rougher than those without conditioning (p = 0.045). Microscopic analysis showed surface alterations on samples conditioned with acid. It is possible to conclude that the group conditioned with hydrofluoric acid showed better adhesive behavior.